2010
DOI: 10.1159/000318836
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Predictors of Clinical Progression among Patients with Dysexecutive Mild Cognitive Impairment

Abstract: Background/Aims: There are few studies that evaluate the clinical outcomes of individuals with non-amnestic mild cognitive impairment (MCI). The purpose of this study was to evaluate baseline predictors of clinical progression after 2 years for patients with dysexecutive MCI (dMCI), a single-domain non-amnestic MCI subgroup. Methods:We evaluated clinical progression in a sample of 31 older adults with dMCI. Clinical progression was defined as a worsening on the Clinical Dementia Rating sum of boxes at the 2-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 83 publications
1
30
0
2
Order By: Relevance
“…Individuals that are classified as amnestic MCI have noticeable recent memory complaints but have no obvious deficits associated with activities of daily living. Many of these individuals transition to AD, although the time course is variable and may occur over a number of years [58, 59]. There was some overlap in the estimation of total synaptic numbers between the three diagnostic groups with a subset of AD and MCI subjects in the range observed for the NCI group.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals that are classified as amnestic MCI have noticeable recent memory complaints but have no obvious deficits associated with activities of daily living. Many of these individuals transition to AD, although the time course is variable and may occur over a number of years [58, 59]. There was some overlap in the estimation of total synaptic numbers between the three diagnostic groups with a subset of AD and MCI subjects in the range observed for the NCI group.…”
Section: Discussionmentioning
confidence: 99%
“…While memory disorder clinics reported that amnestic MCI (aMCI) was the most common form of MCI, it was clear that MCI along with other affected single cognitive domains comprised a small, but significant, component of this clinical presentation. Indeed, people with a clinical diagnosis of MCI comprise a heterogeneous cohort of which those who present solely with memory deficits are classified as single domain aMCI, while those who have a deficit in memory as well as other cognitive domains are categorized as multi-domain MCI (mdMCI) (Johnson et al, 2010; Petersen, 2003). Those with aMCI are at a higher risk of developing AD (Johnson et al, 2010; Petersen, 2003).…”
mentioning
confidence: 99%
“…Indeed, people with a clinical diagnosis of MCI comprise a heterogeneous cohort of which those who present solely with memory deficits are classified as single domain aMCI, while those who have a deficit in memory as well as other cognitive domains are categorized as multi-domain MCI (mdMCI) (Johnson et al, 2010; Petersen, 2003). Those with aMCI are at a higher risk of developing AD (Johnson et al, 2010; Petersen, 2003). However, some people clinically diagnosed with no cognitive impairment (NCI) or with MCI can exhibit SP and NFT pathology equal to or greater that that seen in mild to moderate AD dementia, challenging the pathologically-based idea that these lesions alone cause dementia (Mufson et al 1999; Price et al 2009, Markesbery 2010).…”
mentioning
confidence: 99%
“…O CCLa puro é associado a maior risco de progressão para DA, de maneira que o comprometimento da memória episódica é considerado o sintoma clínico prodomal mais comum de DA (Charchat-Fichman, 2003 (Johnson et al, 2010). O CCLna está associado a maior risco para progressão de demência frontotemporal, além de outras consequências não relacionadas a demência (Forlenza et al, 2013).…”
Section: Taxas De Progressãounclassified
“…O mesmo ocorre quando se começa a identificar e classificar os subtipos: para o subtipo amnéstico, a classificação da BBRC (77%) seguiu o resultado dos critérios expandidos da Clínica Mayo que encontrava um valor bem acima do que estudos recentes (Manly et al, 2005;Petersen et al, 2014) estão encontrando (18,9% contra 5-7%). No caso do subtipo não-amnéstico, o caso se inverte: a prevalência aumenta consideravelmente nos estudos internacionais (Johnson et al, 2010;Pa et al, 2010), chegando a 38%. A BBRC apresentou um valor um pouco abaixo (23%), enquanto a EMAD apresenta um valor um pouco acima (44%), pois ela conseguiu subdividir bem melhor os grupos do que a BBRC, levando a uma classificação mais específica dos grupos.…”
Section: Frequência De Classificação Pelos Instrumentos E Comparação unclassified